Ectopic Location of Permanent Tooth Germ Accompanied by Infraocclusion of Primary Second Molar - Masoumeh Aminizadeh; Fatemeh Jahanimoghadam (Negah Institute for Scientific Communication, 2016)
We report the delayed eruption and infraocclusion of a mandibular second primary molar with ectopic location of the permanent successor. This was a rare case where the second premolar was located to the distal side of the impacted mandibular second primary molar. Early intervention is recommended to manage orofacial disfigurement and prevent consequent problems.